Plasma-polymerized C-60-coated CNT interlayer with physical and chemical functions for lithium-sulfur batteries - Tran Minh Xuan; Ardhi, Ryanda Enggar Anugrah; Liu, Guicheng; Kim, Ji Young; Lee, Joong Kee (ELSEVIER SCIENCE SA, 2020)
The electrochemical application of plasma-induced polymerized fullerene (PC60), wherein C-60-derived radicals play physical and chemical functions, representing an important frontier in fullerene derivatives. We prepared a dual-functional interlayer of a gradationally PC60-coated carbon nanotube (CNT) matrix, where the population of C-60-originating carbon moieties decreased linearly across the CNT@PC60 from the separator to the sulfur electrode in a lithium-sulfur battery (LSB). The three-dimensional CNT@PC60 interlayer acted as both a physical ionic shield, impeding the shuttle effect, and a catalytic immobilizer, enhancing the kinetics of sulfur conversion. The synergistic effectiveness of the dual perm-selective CNT@PC60 interlayers in confining polysulfide species enabled delivery by the LSB with a high specific capacity of 829 mAh g(-1) and an ultra-low decay rate of 0.066% per cycle over 400 cycles at 5C. The role of PC60 in this superior electrochemical performance is the different physical and chemical characteristics of the ends of the interlayer. The PC60-rich side acts as a physical barrier with a mean pore size of 0.7 nm, which enables the penetration of lithium ions only without polysulfide intrusion. Meanwhile, the PC60-poor side formed a catalytic immobilizer because of its higher chemical functionalized degree.
Keywords: LI-S BATTERIES; RAMAN-SPECTROSCOPY; COMPOSITE ANODE; GRAPHENE OXIDE; PORE-SIZE; CARBON; PERFORMANCE; CATHODE; POLYSULFIDES; STABILITY